Structural characterization, antioxidant and anti-uropathogenic potential of biogenic silver nanoparticles using brown seaweed Turbinaria ornata - Raj, C. T. Dhanya; Muthukumar, Krishnan; Dahms, Hans Uwe; James, Rathinam Arthur; Kandaswamy, Surabhi (Frontiers in Microbiology, 2023)
Alternative treatment strategies for urinary tract infections (UTIs) are becoming more necessary due to increasing drug resistance patterns in uropathogens. Nanoparticle-based therapeutics is emerging as a way to treat UTIs. In the present study, using Turbinaria ornata extract, silver nanoparticles (AgNPs) were synthesized, characterized, and their anti-uropathogenic activity was evaluated. The stability and formation of synthesized To-AgNPs were confirmed by UV-visible spectroscopy, FTIR, XRD, SEM and DLS. An FTIR spectrum confirmed the presence of seaweed functional groups in To-AgNPs, a XRD analysis confirmed their crystalline nature, and SEM imaging confirmed their spherical nature with an average size of 73.98 nm with diameters ranging from 64.67 nm to 81.28 nm. This was confirmed by TEM results. DLS determined that the cumulant hydrodynamic diameter of To-AgNPs was 128.3 nm with a PdI of 0.313 and the zeta potential value were found to be –63.3 mV which indicates the To-AgNPs are negatively charged and more stable. DPPH assays were used to assess the antioxidant activity of biosynthesized To-AgNPs, while an agar well diffusion method was used to test the antibacterial activity against uropathogens, including Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis, and Klebsiella pneumoniae. The To-AgNPs showed the highest susceptibility to S. aureus (15.75 ± 0.35 mm) and E. coli (15 ± 0.7 mm) with MIC values of 0.0625 mg/mL and 0.125 mg/mL, respectively in macro broth dilution method and observed considerable membrane damage under CLSM and SEM. To-AgNPs displayed stronger antioxidant and antimicrobial activity, suggesting they may be developed as a new class of antimicrobial agents for treating UTIs.